(untitled) (Journal of the College of Basic Education, 2022)
This topic acquires great importance based on our need and desire to get acquainted with knowledge from the Moroccan media and present in the Moroccan memory in order to get acquainted with it and bring it closer to the forum and try to benefit from the difficult historical experience and stage that accompanied its inception and contributed to the formation and distinction between sincere scholars and others degenerate followers.